Carta de José Celso Barbosa a Roberto H. Todd - Todd, Roberto H.; Celso Barbosa, José (My University, 1921)
Publicación de la entrevista entre Roberto H. Todd y Emmet Montgomery Reily.
Keywords: Montgomery Reily, Emmet, 1866-1954; Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Janer, Julio; Arrillaga Roqué, Rafael; Méndez Santana, Francisco; Feliú, Plácido; Palmieri, Alfredo; Travecier, Carlos; Santaella, Herminio W.